Efektivitas Media Bingo Untuk Pembelajaran Kosakata Bahasa Jepang Pada Siswa SMA - Figa Defri Yuvenza; Rahmi Oktayory wikarya (Omiyage : Jurnal Bahasa dan Pembelajaran Bahasa Jepang, 2023)
Based on researchers' observations, the study is in the background because students often find it difficult to memorize a Japanese vocabulary. The purpose of this study is to know the effectiveness of bingo media for the study of the Japanese vocabulary in high school students. The type of research used in this study is a quantitative study with a pre-design research design. The research design used was one group pretest posttest. The sample in this study is sophomores 1 as many as 20 students. Sampling retrieval in this study uses an impressive sampling technique. The data in this study is the result of pretest and posttest. The instrument used to collect data on an objective test of multiple choice as much as 30 grains of matter. Based on the calibrated test results can be seen from the value of sig (2-tailed) 0,000 < 0.05. H1 is accepted and h0 is denied, which leads to the conclusion that media bingo is significantly effective for the studies of the Japanese vocabulary of sophoma-grade science 1 high school pgri 1 padang. In addition, students have improved their study of Japanese vocabulary after using media bingo. This increase can be seen from an average of 58 pretests and posttests to 86.